The effects of share repurchase announcements on returns in the Malaysia stock market - Tze, San Ong; Pei, San Ng (Thomson, 2018)
This paper examines the market response surrounding the share repurchase announcements of Malaysia Listed Companies from years 2012 to 2016. One sample T-test was carried out to identify the abnormal return in the range before and after 20 days from share repurchase announcements. The result shows a significant positive abnormal return in the day of repurchase announcements and continuously until day 1 after the announcements. Multiple regression analysis was performed in order to identify the firm characteristic of share repurchase. The finding is supported with information asymmetric, which shows that stock market reacts more favorably through the repurchase announcements by small firms than large firms. This study is consistent with the signaling hypothesis that shows share repurchase announcement can be an effective tool in stabilizing the stock market in Malaysia. The finding of this study acts as a useful tool for managers and investors to improve their decisions on share repurchase announcements in Malaysia. Company’s managers can conduct share repurchase announcements that are able to make the stock market react positively in order to generate positive abnormal returns.